The Importance of UACR (Urinary Albumin Creatinine Ratio) Examination in Patients with Diabetes Mellitus Type 2: A Systematic Review - Tetrina Purtaria; Sulistyawati, Sulistyawati (Universitas Ahmad Dahlan, 2024)
Background: Diabetes mellitus is a chronic metabolic condition causing elevated blood glucose levels, leading to microvascular and macrovascular consequences. It is a leading cause of end-stage kidney disease (ESKD) and end-stage renal disease (ESRD). Diabetes causes diabetic nephropathy, which is the leading cause of end-stage renal disease. The urinary albumin-to-creatinine ratio (UACR) is a clinically used tool to evaluate albuminuria and prevent the progression of diabetic nephropathy. ACR measurements are predictive markers for renal outcomes, cardiovascular outcomes, and mortality in diabetics. Microalbuminuria, a condition characterized by 30 to 300 mg/g in spot urine, is an independent predictor of coronary artery disease, cardiovascular disease, and all-cause mortality. This systematic review aimed to understand the role of ACR (albumin creatinine ratio) urine in patients with type 2 diabetes mellitus based on the published article. Method: The systematic review followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and used databases ScienceDirect, PubMed, and Sage Journal to search for articles on urinary albumin creatinine ratio in type 2 diabetes mellitus. The search used keyword, inclusion and exclusion criteria to screen the article. 10 articles met our criteria and were included in this research. Results: ACR (albumin creatinine ratio) levels are linked to cardiovascular risk in patients with diabetes mellitus (DM), and high UACR (urinary albumin creatinine ratio levels are linked to an increased risk of CKD (chronic kidney diseases). The patient's diabetes duration also impacts ACR levels. The KDI is a composite of eGFR (estimated glomerular filtration rate) and ACR risk variables with a clear linear relationship with all three outcomes. It may aid in the identification of high-risk individuals who will benefit the most from prophylactic medications. Conclusion: Patients should be taught how better blood glucose and albuminuria control might help delay the progression of CKD. The male sex is protective; however, most female patients were postmenopausal with low estrogen levels, eliminating any potential renoprotective advantage. Dipsticks may be used for UACR testing, making it more convenient.